Penyelesaian Sengketa Harta Pusaka Tinggi oleh Ninik Mamak Kaum Suku Koto di Pasa Rabaa Nagari Panyalaian Kecamatan X Koto Kabupaten Tanah Datar - Adiguna, Fajar; Ismi, Hayatul; Firmanda S, Hengki (Jurnal Ilmiah Wahana Pendidikan, 2024)
This dispute over high inheritance rice fields occurred between Rusyda Tamin and Ahmad (the biological son of the late Ruqayah, Rusyda's older brother) from the Koto Tribe in Pasa Rabaa Nagari Panyalaian, X Koto District, Tanah Datar Regency. The beginning of this dispute occurred when Ruqayah died in 1996, Ahmad, the biological son of the late Ruqayah, began to control the rice fields inherited from his mother. The rice field is a high pusako treasure that is passed down from generation to generation to daughters. Meanwhile, Mrs. Ahmad (Ruqayah) still has living female parents and a biological sister named Rusyda. In 1998 Rusyda's mother (Lamuna) also entered the presence of God, leaving behind her only daughter, Rusyda. Yeti also experienced a similar case in one tribe. For years, Yeti had never received the results of his rice fields which had been inherited by his biological parents (Zahara, deceased). His rice field is completely controlled by the son (Herman) of his mother's brother. The resolution that was carried out by the Head of the Clan or Ninik Mamak was in deliberation to decide that: "The son of the Mother's clan can enjoy high pusako yields as long as he (the son) is still alive."